Genetic variation and phylogeography of the magpie’s genus Pica in the Holarctic - A. Р. Kryukov (Вавиловский журнал генетики и селекции, 2025)
The theory of Pleistocene refugia is often used to explain the population genetic structure of species. However, it does not fully account for the diversity of species-specific characteristics and natural conditions. The genus Pica, which is widespread in the Holarctic, provides an ideal model for studying phylogeographic patterns in order to better understand processes of diversification and speciation. Markers of mitochondrial DNA remain widely used in phylogeographic studies, despite advances of whole genome techniques. We have summarized published research on the mitochondrial DNA Control Region (CR) variation, based on data from 279 samples which represent the majority of extant taxa across the entire distribution range of the genus. In the phylogenetic trees and networks, we found several cases of reciprocal monophyly among most allopatric species and subspecies, and in addition some examples of paraphyly and polyphyly. Bayesian skyline plots were calculated to explore population dynamics over time. They showed varying longevity of the lineages since their origin or after experiencing a bottleneck, e. g., in the case of the Kamchatka population, as well as unequal rates of expansion. In most cases, speciation followed a geographic model involving expansion and vicariance, sometimes with divergence in refugia. Somewhere, peripatric speciation may have happened due to separation of a marginal populations. By comparing haplotype composition among populations, we traced the origin of the recently established populations on Hokkaido and Kyushu islands from a limited number of colonizers from the mainland. Isolated cases of species in statu nascendi were identified through evidence of incomplete lineage sorting, leading to paraphyly, or signs of limited unidirectional interspecies introgression of nuclear genes in secondary contact zones. Several hypotheses regarding the formation of the magpie´s range are proposed. Various evolutionary scenarios found in the genus Pica were compared to those reported for the other bird species in a number of literature sources.